Extended robot‐assisted laparoscopic prostatectomy and extended pelvic lymph node dissection as a monotherapy in patients with very high‐risk prostate cancer Patients. (25th September 2021) - Miura, Noriyoshi; Sugihara, Naoya; Funaki, Keisuke; Kakuda, Toshio; Koyama, Kanae; Watanabe, Ryuta; Sawada, Yuichiro; Noda, Terutaka; Nishimura, Kenichi; Fukumoto, Tetsuya; Miyauchi, Yuki; Kikugawa, Tadahiko; et al.
Abstract: Background: Patients with very‐high‐risk prostate cancer (VHRPCa) have earlier biochemical recurrences (BCRs) and higher mortality rates. It remains unknown whether extended robot‐assisted laparoscopic prostatectomy (eRALP) without neoadjuvant or adjuvant therapy can improve the outcomes of VHRPCa patients. We aimed to determine the feasibility and efficacy of eRALP as a form of monotherapy for VHRPCa. Methods: Data from 76 men who were treated with eRALP without neoadjuvant/adjuvant therapy were analyzed. eRALP was performed using an extrafascial approach. Extended pelvic lymph node (LN) dissection (ePLND) included nodes above the external iliac axis, in the obturator fossa, and around the internal iliac artery up to the ureter. The outcome measures were BCR, treatment failure (defined as when the prostate‐specific antigen level did not decrease to <0.1 ng/ml postoperatively), and urinary continence (UC). Kaplan–Meier, logistic regression, and Cox proportional‐hazards model were used to analyze the data. Results: The median operative time was 246 min, and median blood loss was 50 ml. Twenty‐one patients experienced postoperative complications. Median follow‐up was 25.2 months; 19.7% of patients had treatment failure. Three‐year, BCR‐free survival rate was 62.0%. Castration‐resistant prostate cancer‐free survival rate was 86.1%. Overall survival was 100%. In 55 patients who had complete postoperative UC data, 47 patients (85.5%) recovered from their UC within 12 months. Clinical stage cT3b was an independent preoperative treatment failure predictor ( p = 0.035), and node positivity was an independent BCR predictor ( p = 0.037). The small sample size and retrospective nature limited the study. Conclusions: This approach was safe and produced acceptable UC‐recovery rates. Preoperative seminal vesicle invasion is associated with treatment failure, and pathological LN metastases are associated with BCR. Therefore, our results may help informed decisions about neoadjuvant or adjuvant therapies in VHRPCa cases. Precis: Extended robot‐assisted laparoscopic prostatectomy and extended pelvic lymph node dissection without adjuvant therapy is safe and effective for some patients with very‐high‐risk prostate cancer. The clinical stage and node positivity status predicted monotherapy failure, which may indicate good adjuvant therapy candidate. Abstract : Extended robot‐assisted laparoscopic prostatectomy and extended pelvic lymph node dissection without adjuvant therapy is safe and effective for some patients with very‐high‐risk prostate cancer. The clinical stage and node positivity status predicted monotherapy failure, which may indicate good adjuvant therapy candidates.